Health Risks Associated With Sources of Water: An Exploratory Study From Turag-Tongi Riparian Areas, Bangladesh: Health risk associated with sources of water - Prodhan , Shamima; Nasreen, Mahbuba (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The present study aims to investigate the available water sources for drinking and domestic purposes and their relationship with the occurrence of diseases in a given community. To accomplish this, 1826 households in the Turag River area of Tongi at twelve different locations were surveyed. Six focus group discussions (FGDs) and twelve key informant interviews (KIIs) were also conducted in six different Turag River locations. Data on water quality has been gathered from various government surveys (BNDWQS, 2011; BBS, 2017; SVRS, 2019, etc.), international reports (WHO, World Bank, etc.), individual studies, and other relevant sources. Of all the recorded (13) drinking water sources, motorized tubewells were the most common and were used by 73.8 percent of respondents. Other sources include pipe connections into the yard (16.7%) and dwelling (4.5%), deep and shallow tube wells (2.6%), public tap water (2.1%) etc. The study also revealed that a notable percentage (2.8%) of the survey population still depended on open sources such as rainwater, rivers, lakes, ponds, etc., for drinking and domestic purposes. The respondents also reported the presence of yellow crust (iron) and other unwanted components in their water sources, with foul odors and unpleasant tastes. It has also been documented that the communities have been suffering from various diseases, such as diarrhea, skin diseases, dysentery, malaria, jaundice, typhoid, tuberculosis, pneumonia, cholera, etc. diseases over the past year. The Spearman's rho (ρ’s) test showed significant associations between these diseases and the water sources. The issues identified by the present study are likely to aid policymakers in including water and health concerns in national policy and ensuring access to sustainable water resources, aligning with SDGs 6.1, 6.3, and 6.4. J. Asiat. Soc. Bangladesh, Sci. 49(2): 121-138, December 2023